The Effect of Accelerator on Mechanical and Swelling Properties of NBR/EPDM/BIIR Composite - hesty eka mayasari; agung yanuar wirapraja (Balai Riset Dan Standardisasi Industri Surabaya, 2021)
Composite is a material made from two or more materials. Composite has better properties than a single material. Additive or compatibilizer is usually needed to make a homogeneous composite. This research used Nitrile Butadiene Rubber (NBR) and Ethylene Butadiene Monomer Rubber (EPDM) as the primary matrix with Bromobutyl Rubber (BIIR) as the compatibilizer. The blending of composite rubber was done using the two-roll mill. This research studied the effect of various accelerators (DPG, MBT, CBS, TMTD, and ZDEC) in NBR/EPDM/BIIR composite. The mechanical and swelling properties of the composite were studied using tensile strength tester and swelling test. The CBS gives the highest tensile, elongation at break, and tear strength. CBS gives the lowest swelling percentage. CBS is the proper accelerator for improving the mechanical and swelling properties of the NBR/EPDM/BIIR composite.